Implementasi Metode Least Square untuk Peramalan Persediaan Barang Pada Sistem Inventori CV. Tre Jaya Perkasa - Tulsi Yasmi Tulsi; Aldo Erianda; Rita Afyenni (JITSI : Jurnal Ilmiah Teknologi Sistem Informasi, 2022)
Entering the era of society 5.0 has brought many changes in various sectors, one of which is in the business sector. Competition in the business world and the rapid development of information technology, requires companies to make changes in business processes, one of which is CV. Tre Jaya Perkasa which is engaged in the distribution of goods such as snacks, drinks and daily needs. CV. Tre Jaya Perkasa is located in Solok, West Sumatra, Indonesia. CV. Tre Jaya Perkasa already has more than 1000 customers who take goods for resale. The number of sales transactions will affect the inventory in the warehouse. Inventory control is important for distributor companies to reduce stockouts for certain products. With this, a system is needed that is able to predict inventory for the future. For forecasting inventory, the Least Squares method can be applied. The Least Square method is a method used to determine trend equation data including Time Series analysis with two cases, namely even and odd case data. To measure forecast errors using this study the Mean Absolute Percentage Error (MAPE) method was used. This system is built using the Yii2 framework and the testing system uses Black Box Testing.